Pengembangan Desain Awal Model Resolusi Konflik dalam Pembelajaran IPS - Suprapto, Wasis; Maftuh, Bunyamin; Sjamsuddin, Helius; Malihah, Elly (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The conflict in West Kalimantan is one of the negative impacts of ethnic diversity in Indonesia. To prevent the recurrence of similar conflicts, the participation of various parties, including the education sector, is required by developing conflict resolution education. This article aims to examine three things, namely (1) the theoretical design supporting the model from the educational aspect, (2) examining the initial design of the model, and (3) examining the design implementation of the model. The research was studied using the Sukmadinata approach which simplifies the development research stages of Borg Gall. The results show that (1) there are three educational theories used to develop conflict resolution models in social studies learning, namely progressivism theory, reconstruction theory, and humanist theory. (2) The development of the initial design of the conflict resolution model in social studies learning includes five aspects, namely syntax, social systems, management systems, support systems, and instructional and accompaniment impacts. (3) The design of the implementation of the conflict resolution model in social studies learning includes planning, targets, and actions.